Dreams That Stuff is Made of : The Most Astounding Papers on Quantum Physics and How they Shook the Scientific World - Hawking, Stephen (Philadelphia : Running press, 2011)
God does not play dice with the universe. So said Albert Einstein in response to the first discoveries that launched quantum physics, as they suggested a random universe that seemed to violate the laws of common sense. This 20th-century scientific revolution completely shattered Newtonian laws, inciting a crisis of thought that challenged scientists to think differently about matter and subatomic particles.The Dreams That Stuff Is Made Of compiles the essential works from the scientists who sparked the paradigm shift that changed the face of physics forever, pushing our understanding of the universe on to an entirely new level of comprehension. Gathered in this anthology is the scholarship that shocked and befuddled the scientific world, including works by Niels Bohr, Max Planck, Werner Heisenberg, Max Born, Erwin Schrodinger, J. Robert Oppenheimer, Richard Feynman, as well as an introduction by today's most celebrated scientist, Stephen Hawking.
Keywords: Quantum physics; General Science